2016
DOI: 10.1310/hpj5110-856
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Business Plan for Critical Care Pharmacy Services

Abstract: Critical care medicine has grown from a small group of physicians participating in patient care rounds in surgical and medical intensive care units (ICUs) to a highly technical, interdisciplinary team. Pharmacy's growth in the area of critical care is as exponential. Today's ICU requires a comprehensive pharmaceutical service that includes both operational and clinical services to meet patient medication needs. This article provides the elements for a business plan to justify critical care pharmacy services by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… Implementation and demonstration of cost-savings initiatives related to medications.  Service as a leader for critical care pharmacy services [28][29][30].…”
Section: R E T R a Cmentioning
confidence: 99%
See 1 more Smart Citation
“… Implementation and demonstration of cost-savings initiatives related to medications.  Service as a leader for critical care pharmacy services [28][29][30].…”
Section: R E T R a Cmentioning
confidence: 99%
“…Service as a leader for critical care pharmacy services [ 28 - 30 ].…”
Section: Pharmacists' Role In Critical Carementioning
confidence: 99%
“…Some have suggested that the time has come to discard the need for ICU pharmacists to justify their value and instead for ICUs and patients to expect the presence of direct pharmacy services either through accreditation standards or reimbursement ( 19 ). The multidisciplinary community of critical care must seek other modes and sources of financial support and explore payment for critical care pharmacy services ( 20 ).…”
Section: Discussionmentioning
confidence: 99%